Treatment of Graves’ Disease With a Combination of Low Iodine Diet and Potassium Iodide Plus Radioactive Iodine Treatment - Ebrahim, Ismail (J Endocr Soc, 2021)
Introduction: Graves’ disease (GD) is usually treated with radioactive iodine I(131) (RAI), thionamide or surgery. Of these, RAI remains the safest and most efficacious treatment. We report 3 patients with GD who were treated with low iodine diet (LID), followed by RAI and subsequent potassium iodide (SSKI) administration.Case series:Patient 1 - A 50-year-old male presented with weight loss, heat intolerance and palpitations. Physical examination: HR 120 bpm, BP 110/80mmHg, no evidence of thyroid orbitopathy. Thyroid: 50 grams diffusely enlarged and brisk DTR. Lab findings: TSH 0.001, FT4 4.2, total T3 410, TSI 172. A thyroid scan revealed diffuse uptake 72% at 4-hours. He was diagnosed with GD and treated with methimazole. Three weeks later a CBC showed an absolute neutrophil count 820. After discontinuing methimazole, he was placed on prednisone 40mg daily and LID. Two weeks later (24-hours urine iodine <50 mcg), he received 15mCi I(131). 72 hours later he was administered SSKI one drop BID for 3 days. Four weeks after RAI, TFT was normal. Two months later, he required levothyroxine treatment for hypothyroidism. Patient 2 - A 23-year-old female presented with weight loss and nervousness. Physical examination revealed HR 110 bpm, BP 100/70 mmHg, no thyroid orbitopathy, a diffusely enlarged thyroid. Serum TSH <0.005, FT4 3.9, total T3 398, TSI 149. Thyroid uptake showed 70% at 24-hours. Patient was started on methimazole and atenolol. Four weeks later she developed severe generalized erythematous rash. After treating with prednisone for one week she was placed on LID and treated with 15 mCi I(131). Six weeks later TSH was 0.4 with a free T4 of 1.8 and four months later she required levothyroxine therapy for hypothyroidism. Patient 3 - A 40-year-old male presented with atrial fibrillation and hyperthyroidism. Patient received treatment for atrial fibrillation and physical examination confirmed heart rate 78 (on treatment), no evidence of thyroid orbitopathy, and diffusely enlarged thyroid. Serum TSH <0.005, FT4 3.1, total T3 298, TSI 231. Thyroid scan was consistent with GD with a 24-hr uptake of 62%. He refused to take methimazole due to fear of adverse side effects. After placing him on prednisone along with LID for 2weeks, he was treated with I(131) 15 mCi. 72 hours later he received SSKI one drop BID for 3 days. Prednisone was discontinued 2 weeks later. Six weeks following treatment, TSH was 1.1 with FT4 1.32. Patient remained euthyroid for the next 12 months of follow up. Discussion: LID given before RAI therapy has a potential of depleting total iodine pool which can increase the I(131) uptake in the thyroid gland and facilitate β-radiation to the thyroid gland. SSKI following RAI can improve retention of I(131) in the thyroid gland and reduce the recycling of radioactivity between the thyroid and the blood. In summary, a LID prior to RAI and SSKI following RAI treatment be beneficial in certain patients with GD.